Coffee Roasting Training To Improve Production Quality And Efficiency Of Ksu Ketakasi Coffee Business - Zainur Ridlo, Muhammad; Abidin , Asroful; Muliasari , Risa Martha; Rizkina, Fitriana Dina (Universitas Muhammadiyah Jember, 2023)
Competition in the coffee business is increasingly widespread with high interest from coffee consumers ranging from retail consumers to industrial scale. The interests of coffee consumers vary according to consumer needs. The level of diversity in coffee consumer needs means that coffee bean business activists must improve the quality of their production and increase production efficiency. KSU Ketakasi is a cooperative that supports coffee farmers on the slopes of Argopuro, specifically coffee farmers from Sidomulyo Village, Silo District, Jember Regency. KSU Ketakasi is developing its business line starting from selling raw beans, roasted beans, to ground coffee, one of the processes that influences the sustainability of this process is the coffee bean roasting process. The correct process of roasting coffee beans is considered capable of improving the quality of production from coffee entrepreneurs and selecting the right roasting machine is also a benchmark for increasing efficiency in the production process. The following activities carried out in community service include providing education to farmer members of the KSU Ketakasi cooperative so that they can process coffee beans with good quality and be able to increase the efficiency of the roasting process by using a smart eco roasting machine.